Revision of Bondariella Hustache & Bondar (Coleoptera: Curculionidae), with descriptions of the first species from the Amazon and notes on natural history - Valente, Roberta De Melo; Cordeiro, Mariano Brandão Júnior (Zootaxa, 2015)
Bondariella Hustache & Bondar, 1942 is revised. In addition to the redescription of the genus and its four previously known species, we report and describe the first species from the Amazonian region: Bondariella rudicula sp. nov. and Bondariella crenata sp. nov. We also provide a key to the species, illustrations and notes on natural history. All six species of Bondariella have been collected on palm flowers from Brazil, with the previously known species having only been recorded from species of Syagrus Mart. from the Atlantic Forest and Caatinga biomes. The two new species have only been recorded from species of Euterpe Mart. from the Amazon biome. Future work may prove if the associations with Syagrus and Euterpe are specific to the biomes.